Design and implementation of automatic fish feeder (AFF) using microcontroller powered by solar cell: A Contribution to the fish farmers - Susilawati Susilawati; Aditya Nugraha; Slamet Rahayu; Ferdi Fathurohman; Oyok Yudiyanto; Azhis Sholeh Buchori (Universitas Muhammadiyah Magelang, 2023)
This study aims to design and test an automatic fish feeder (AFF) controlled by a microcontroller with an electricity supply from a solar cell. To build a reliable and accurate system, input data is collected for design, followed by system development, feasibility analysis, and performance testing. The test results show that AFF works according to the settings of the microcontroller, where the servo motor can open and close the feed channel periodically, three times a day. The feeding schedule is set at 07.00, 12.00, and 16.00. In addition, fundamental indicators including feed conversion ratio (FCR) and feed efficiency (FE) are showing positive results. Through the application of AFF which replaces manual feeding, the FCR is obtained at 1.15 from the initial value of 1.44. Meanwhile, FE increased from 69.4% to 86.8%. Technically, AFF is suitable for use by tilapia and carp farmers.